2018
DOI: 10.4136/ambi-agua.1999
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in waters used for human consumption and crop irrigation

Abstract: The consumption of contaminated water is a major source of heavy metal contamination in humans and animals. This study therefore aimed to assess Cd, Cu, Mn, Ni, Pb, and Zn levels in water used for human and animal consumption and vegetable crop irrigation in Camocim de São Félix, Pernambuco, Brazil. Water samples were collected on the studied farms from an artesian well and reservoirs used for human and animal consumption as well as for crop irrigation. The results showed that concentrations of Cd (> 0.001 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…The content of As and Pb in irrigation water comply with the norms and are found below those reported for Bangladesh of 0.134 and 0.119 mg•L -1 , respectively [10]. Cd levels between 0.041 to 0.058 mg L -1 were reported by [21] in water samples, which may be due to excessive use of phosphate fertilizers, in our study only site N presented Cd traces (0.029 mg•L -1 ). The same authors found Ni levels in the water samples from 1.85 to 3.31 mg L -1 , above maximum allowable limit of 0.025 mg L -1 .…”
Section: Heavy Metals In Watersupporting
confidence: 70%
“…The content of As and Pb in irrigation water comply with the norms and are found below those reported for Bangladesh of 0.134 and 0.119 mg•L -1 , respectively [10]. Cd levels between 0.041 to 0.058 mg L -1 were reported by [21] in water samples, which may be due to excessive use of phosphate fertilizers, in our study only site N presented Cd traces (0.029 mg•L -1 ). The same authors found Ni levels in the water samples from 1.85 to 3.31 mg L -1 , above maximum allowable limit of 0.025 mg L -1 .…”
Section: Heavy Metals In Watersupporting
confidence: 70%
“…In this way, it can be noticed that the contribution of domestic sewage and agricultural activities to the concentrations of heavy metals in P1 occurs due to the high concentration of Hg, Cu and Zn, which have domestic sewage as a common source (Jackson, 1992), and agricultural activities, through the use of pesticides, fertilizers, insecticides, among others (Gonçalves Júnior et al, 2014;Nacke et al, 2013;Silva et al, 2016;2018).…”
Section: Resultsmentioning
confidence: 99%
“…Esta contaminação pode prejudicar a qualidade das águas e a saúde humana, além de gerar impactos ambientais. É principalmente através do consumo de águas com metais tóxicos que ocorre a contaminação dos seres humanos e dos animais (AMIN et al, 2013;SILVA et al, 2018. ) Essa contaminação pode se dar de forma direta pelo consumo de água e de forma indireta por meio das cadeias alimentares, devido à grande capacidade de bioacumulação ou magnificação trófica desses elementos.…”
Section: Introductionunclassified